Pavlo Mitrofanovych Ustymenko as a botanist and forester: strokes of a creative portrait of the scientist for the 40th anniversary of his scientific activity (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
The publication highlights the main results of the scientific activity of Pavlo Mitrofanovich Ustymenko – Ukrainian geobotanist and forest scientist, well known in the Eastern Europe, on the occasion of his 70th anniversary and 40th anniversary of his scientific activity. P.M. Ustymenko was born in 8 February 1953 in Khodzheyli (Xojeli) city (Republic of Karakalpakstan, Uzbekistan), studied in 1961–1968 at Oblapy school of Kovel district and in 1968–1970 at Lesya Ukrainka school № 3 in Kovel town of Volyn region of Ukraine. In 1975 he was graduated from the Faculty of Forest science of Ukrainian Agricultural Academy. In 1975–1977 P.M. Ustymenko worked as deputy director at Saky district of Yevpatoriya Forest-Meliorative station (Authonomic Republic of Crimea), in 1978–1979 – as a master of green economy of Minskyi district of Kyiv city. Since 1979 Pavlo Mitrofanovych works at M.G. Kholodny Institute of Botany of National Academy of Sciences of Ukraine (1979–1985 – engineer, 1985–1986 – senior engineer, 1986–1989 – junior research fellow, 1989–1995 – research fellow, 1995–2006 – senior research fellow, 2006–nowadays – leading researcher). His first scientific publications were devoted to the studying of the plant cover of the projected National Nature Park «Mezynskyi» in Chernihiv region of Ukraine. The contribution of P.M. Ustymenko to the development of Ukrainian researching of rare species and plant communities is extremely important. P.M. Ustymenko determined and analyzed the phytocoenotaxonomic diversity of the vegetation of natural regions of Ukraine from the point of view of their phytosozological value. The contribution of the scientist to the preparation of the «Green Data Book of Ukraine» (2009), which became not only a fundamental scientific monograph, but also received the status of an official state document in Ukraine, is solid. Despite his versatile scientific interests P.M. Ustymenko mainly focused on the studying of the forest vegetation. The scientist summarized the syntaxonomic structure of the forest vegetation of Ukraine, compiled a prodromus of its associations and participated in the development of scientific bases for the selection and the protection of their particularly valuable natural forest complexes. P.M. Ustymenko acted as a leading expert during the study of the plant diversity of the Synevyr National Nature Park with the aim of identifying areas of virgin beech forests and including them in the UNESCO World Heritage Sites.
Keywords: Bibliography, botany, phytosociology, forest science, Ukraine.